The essay film : dialogue, politics, utopia - Papazian, Elizabeth Astrid; Eades, Caroline (London: Wallflower Press, 2016)
"With its increasing presence in a continuously evolving media environment, the essay film as a visual form raises new questions about the construction of the subject, its relationship to the world, and the aesthetic possibilities of cinema. In this volume, authors specializing in various national cinemas (American, Cuban, French, German, Israeli, Italian, Lebanese, Russian) and critical approaches (historical, aesthetic, postcolonial, feminist, philosophical) explore the essay film and its consequences for the theory of cinema while building on and challenging existing theories. Taking as a guiding principle the essay form's dialogic, fluid nature, this volume examines the potential of the essayistic to question, investigate, and reflect on all forms of cinema--fiction film, popular cinema, documentary, video installation, and digital essay. A wide range of filmmakers are covered, from Dziga Vertov (Man with a movie camera), Chris Marker (Description of a struggle), Nicoláa Guillén Landrián (Coffea arábiga), Pier Paolo Pasolini (Notes for an African Oresteia), Chantal Akerman (News from home), Mohammed Soueid (Civil war), Claire Denis (L'intrus), and Terrence Malick (The tree of life), among others. This volume argues that the essayistic in film--as process, as experience, as experiment--opens the road to key issues faced by the individual in relation to the collective, but can also lead to its own subversion, as a form of dialectical thought that gravitates towards crisis"--Back cover.
Introduction. Dialogue, politics, utopia / Elizabeth A. Papazian and Caroline Eades -- The essay film as dialogue. Essayism and contemporary film narrative / Timothy Corrigan ; Essaying the forms of popular cinema : Godard, Farocki and principle of shot/countershot / Rick Warner ; The practice of strangeness : L'intrus, from Jean-Luc Nancy (2000) to Claire Denis (2004) / Martine Beugnet ; Cinéma-vérité and Kino-pravda : Rouch, Vertov and the essay form / Caroline Eades and Elizabeth A. Papazian -- The essay film as politics. Notes for a revolution : Pascolini's postcolonial essay films / Luca Caminati ; Chris Marker's Description of a struggle and the limits of the essay film / Eric Zakim ; A woman with a movie camera : Chantal Akerman's essay films / Anne Eakin Moss ; 'What does it mean today to be a communist?' : Nanni Moretti's Palombella rossa and La cosa as essay films / Mauro Resmini -- The essay film as utopia. Mohamed Soueid's cinema of immanence / Laura U. Marks ; Inside/outside : Nicolasito Guillén Landrián's subversive strategy in Coffea arábiga / Ernesto Livon-Grosman ; American essays in how to build a home : Thoreau, Mekas, Proenneke / Oliver Gaycken ; 'to speak, to hold, to live by the image' : notes in the margins of the new videographic tendency / Luka Arsenjuk -- Afterword. The idea of essay film / Laura Rascaroli.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Essay films